Estimation and simulation of decoy state parameters for Practical Quantum Key Distribution (QKD) - Ali, Abdullah Hassan Ahmed (Kulliyyah of Engineering, International Islamic University Malaysia, 2013)
In this dissertation, an estimate of the decoy state parameters method based on BB84 and SARG04 protocol is presented to improve the performance of Quantum Key Distribution (QKD). This method gave different lower bounds of the fraction of the single-photon counts, the upper bound quantum bit error rate (QBER) of single-photon pulses, and the lower bound of key generation rate for both BB84 and SARG04 protocols. It also gave the lower bounds of the fraction of the two-photon counts, the upper bound QBER of the two-photon, and the lower bound of the key generation rate for the SARG04. The fiber-based QKD was simulated using the proposed method for the BB84 and SARG04. The numerical simulation showed the optical fiber- channel QKD system, using the proposed method for the BB84 which was able to achieve both a higher secret key rate and greater secure distance than that of the SARG04. The simulation results showed that the maximum distance that is achieved by QKD system using the proposed decoy state method for the BB84 is greater than the SARG04 for both fiber-based QKD system by at least 10 km. Comparing the results, it is observed that the proposed method for the BB84 with a fiber-based QKD system was 10 times higher in secret key generation rates than the SARG04. Therefore, the BB84 improved the practical performance of QKD system.